Procesamiento de un alimento peletizado a base de pasto, forraje y maíz duro, como fuente de proteína y energía, en la alimentación de terneras entre 3 a 7 meses de edad. - Amador da Gama, Jorge David (2014)
For the development of this research, the final results of four types of feeding for calves 3-7 months of age, which partially replaced the commercial concentrate were studied with a pellet made from a forage mixture composed of ryegrass perennial (Lolium perenne L.), bluegrass (Dactylis glomerata), white clover (Trifolium repens), red clover (Trifolium pratense) and kikuyu (Pennisetum clandestinum Hochst), over hard ground corn in final weight gain of calves and economic analysis of treatments. The animals were grouped into four (4) groups of three calves each, and treatments were randomized within each group. The treatments in observation were treatment 1 commercial feed, treatment 2 , 80% commercial feed + 20% pellet prepared, treatment 3, 70% commercial feed + 30% pellet prepared and treatment 4, 60% balanced commercial + 40% pellet prepared. The experiment had two phases, the first was in the laboratory where the pellet prepared was previously analyzed and was determined that it had the nutritional requirements for growing heifers. The second phase was done on the ranch, where they supplied the animal feed in each treatment...